PHILOSOPHICAL AND SOCIOCULTURAL DIMENSIONS OF PERSONALITY PSYCHOLOGICAL SECURITY - O. Y. Blynova; L. S. Holovkova; O. V. Sheviakov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The dynamics and pace of social and economic transformations that are characteristic of modern society, lead to an increase in tension and the destruction of habitual stereotypes – ideals, values, norms, patterns of behaviour that unite people. These moments encourage us to rethink the understanding of "security" essence, in particular, psychological, which emphasizes the urgency of its study in the philosophical and sociocultural coordinates. Theoretical basis of the research is based on the philosophical methodology of K. Jaspers, E. Fromm and the A. Maslow’s psychological approach to understanding of a person. Originality. Psychological security is considered at different levels: first and foremost, society is a characteristic of social security, that is an analysis of how today’s social technologies, social changes affect the quality of life of the country’s population; secondly, the social environment – the family, the immediate environment, reference groups, training teams; thirdly, a person is an experience of his own security-insecurity, when it is possible to talk about the manifestations of psychological violence, when certain behavioral acts contribute to the violation of the security of the other or to self-destruction. It is found out that the knowledge of psychological security is closely connected with the socio-historical conditions of being, with the level of development of material and spiritual culture, with the interests and values prevailing in society, which determines its ontological, epistemological and axiological features. The presented issue is considered in the correlation of psychological security with types of scientific rationality – classical, nonclassical and post-nonclassical approaches, within the framework of which various perspectives, aspects, forms and types of psychological security are studied. Conclusions. The concept of security requires a systematic description of its manifestations, types, levels, concepts: security as the absence of dangers (based on the principle of dichotomy, that is, a certain whole consisting of two opposite parts, in this case, the whole is human existence); security as a certain activity to ensure or to prevent any threats or dangers (activity approach); security as a conscious necessity, the value of the individual. The study systematizes various ideas about psychological security in accordance with the logic of scientific knowledge: in the mainstream of classical, non-classical and post-nonclassical approaches.